City of Lost Souls - Clare, Cassandra (New York : Margaret K. McElderry Books, 2012)
When Jace vanishes with Sebastian, Clary and the Shadowhunters struggle to piece together their shattered world and Clary infiltrates the group planning the world's destruction.
Keywords: Supernatural -- Fiction; Demonology -- Fiction; Magic -- Fiction; Vampires -- Fiction; New York (N.Y.) -- Fiction; Horror fiction